주민참여형 마을녹화사업의 사회적 자본 형성 모형 - 서울시 생활권녹화사업을 대상으로 - 이애란; 조세환; Lee, Ai-Ran; Cho, Se-Hwan (Ecology and Resilient Infrastructure, 5(1), 2018)
Social, economic and environmental problems caused by rapid urbanization have been recently overcome by various civic participation projects. Local governance and resident - led partnership through field - based cooperative operating systems from urban regeneration to village projects are considered success factors. Among these, the village greening project which directly affects the residents and requires spontaneity requires the role and cooperation of the various participating actors due to the sharing of public space and private space. Social capital plays a key role in the sustainability and participation of the above - mentioned business as a relational capital centered on trust and participation, network and norms. Therefore, empirical research is needed. In this study, basic research was carried out to build a formation model of social capital in participation - type greening project expanding urban green space system to living area. We analyzed the elements of participation, the components of business progress, and the factors of social capital formation through literature review and in - depth interviews with participating experts. The purpose of this study is to provide basic data of social capital formation model for analyzing sustainability and activation strategies in the future. 급격한 도시화로 인한 사회, 경제 그리고 환경적 문제들이 최근 다양한 시민 참여형사업으로 극복되고 있다. 이는 도시재생에서 마을 사업에 이르기까지 현장중심의 협력적 운영체계를 통한 지역 거버넌스와 주민주도의 파트너십이 성공 요소로 여겨지고 있다. 이 중 거주민에게 직접적으로 영향을 주고 자발성이 필요한 마을녹화사업은 공적 공간과 사적 공간의 공유로 인해 다양한 참여주체들의 역할과 협력이 요구된다. 사회적 자본은 신뢰와 참여, 네트워크와 규범 등을 중심으로 한 관계자본으로 위 사업의 지속가능성과 참여의 활성화에 핵심역할을 담당함에 따라 이에 대한 실증적 연구가 요구되는 실정이다. 본 연구에서는 도시의 녹지 체계를 생활권까지 확대하는 참여형 녹화사업에 있어 사회적 자본의 형성 모형을 구축하기 위한 기초연구를 수행하였다. 참여의 주체 유형과 사업 진행의 구성요소, 사회자본 형성의 분석 요소를 문헌조사와 참여 전문가 심층인터뷰를 통해 추출하고 검증하였다. 이는 추후 도시의 참여형 생활권녹화확산에 지속가능성과 활성화전략을 실증적으로 분석하기 위한 사회적 자본 형성 모형의 기초자료를 마련하기 위함이다.